A tissue-mimicking prostate phantom for 980 nm laser interstitial thermal therapy. (1st January 2019) - Geoghegan, R.; Santamaria, A.; Priester, A.; Zhang, L.; Wu, H.; Grundfest, W.; Marks, L.; Natarajan, S.
Abstract: Purpose: To develop a phantom with optical and thermal properties matched to human prostate. This phantom will provide a platform for the development and characterization of 980 nm laser interstitial thermal therapy (LITT) systems. Methods: A polyacrylamide gel was doped with Naphthol Green B, Intralipid, and Bovine Serum Albumin (BSA). The necessary concentration of each ingredient was determined by measuring the optical properties via fluence measurements and light diffusion theory. LITT was then performed under the same conditions as a previous clinical trial in which temperature was monitored via a thermal probe. The thermal data and induced coagulation zone were compared to clinical data to illustrate the similarity between the phantom and patient. LITT was also performed under magnetic resonance thermometry (MRT). Results: The requisite concentrations of Naphthol Green B, Intralipid and BSA were found to be 0.144% (w/v), 8.06% (v/v) and 31.4% (v/v) respectively. In the native state, the absorption coefficient and reduced scattering coefficient ( μ s ′ ) were found to be 0.66 ± 0.06 cm −1 and 8.27 ± 0.50 cm −1 respectively, with μ s ′ increasing to 17.63 ± 1.41 cm −1 after coagulation. The thermal response of the phantom was similar to that observed clinically with maximum thermal probe measurements of 64.2 °C and 66.9 °C respectively. The shape of the induced coagulation zone was qualitatively and quantitatively similar to the MRT zone of elevated temperature and the coagulation zone observed clinically. Conclusions: A phantom which simulates optical and thermal response to 980 nm LITT was constructed and demonstrated to be similar to human prostate.